1969
DOI: 10.1111/j.2517-6161.1969.tb00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Exact Bayesian Analysis of a 2 × 2 Contingency Table, and Fisher's “Exact” Significance Test

Abstract: Summary A relationship is derived between the posterior probability of negative association of rows and columns of a 2 times 2 contingency table and Fisher's “exact” probability, as given in existing tables for testing the hypothesis of no association of rows and columns. The result for the 2 times 2 table is generalized to provide the posterior probability that one discrete‐valued random variable is stochastically larger than another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 7 publications
2
86
0
Order By: Relevance
“…As in the independent samples case studied by Altham (1969), this is a Bayesian P -value for a prior distribution favoring H 0 . If α 12 = α 21 = γ, with 0 ≤ γ ≤ 1, Altham showed that this is smaller than the frequentist P -value, and the difference between the two is no greater than the null probability of the observed data.…”
Section: Comparing Two Matched Binomial Samplesmentioning
confidence: 97%
See 3 more Smart Citations
“…As in the independent samples case studied by Altham (1969), this is a Bayesian P -value for a prior distribution favoring H 0 . If α 12 = α 21 = γ, with 0 ≤ γ ≤ 1, Altham showed that this is smaller than the frequentist P -value, and the difference between the two is no greater than the null probability of the observed data.…”
Section: Comparing Two Matched Binomial Samplesmentioning
confidence: 97%
“…See Berry (2004) for a recent exposition of advantages of using a Bayesian approach in clinical trials. Weisberg (1972) extended Novick and Grizzle (1965) and Altham (1969) to the comparison of two multinomial distributions with ordered categories. Assuming independent Dirichlet priors, he obtained an expression for the posterior probability that one distribution is stochastically larger than the other.…”
Section: Tests Comparing Two Independent Binomial Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Exact results for the posterior distribution of the attributable risk or any of the other measures of difference are complex and involve sums of hypergeometric probabilities (Altham 1969, Hashemi et al 1997. However the marginal posterior distribution of any parametric function of p 1 and p 2 can be simulated directly, by generating N realizations from the posterior distributions of p 1 and p 2 , and calculating the appropriate function (Tanner 1996).…”
Section: The 2 × 2 Table For Randomized Clinical Trialsmentioning
confidence: 99%